Tillage and phosphorus management in maize (Zea mays) under maize-wheat cropping system - N, HARISH M; CHOUDHARY, ANIL K; DASS, A; SINGH, V K; POONIYA, V; T, VARATHARAJAN (The Indian Journal of Agricultural Sciences, 2021)
A field experiment was conducted during kharif 2018–19 under maize-wheat cropping system (MWCS) to study the effect of 4 crop-establishment and tillage management (CETM) practices [FBCT–FBCT, Flat bed–conventional tillage (FBCT) both in maize & wheat; RBCT–RBZT, Raised bed–CT (RBCT) in maize & RB–zero tillage (RBZT) in wheat; FBZT–FBZT, FBZT in both crops; PRBZT–PRBZT, Permanent-raised bed–ZT (PRBZT) in both crops], and 5 P-fertilization practices in both crops [P100: 100% (basal); P50+2FSP: 50% P (basal) + 2 foliar-sprays of 2% DAP (2FSP); P50+PSB+AMF: P50+PSB+AM-fungi; P50+PSB+AMF+2FSP: P50+PSB+AMF+2FSP; P0: No-P (P0) with 100% NK as control] on maize growth and yield. Results revealed that CETM practices exhibited significant influence on growth parameters with highest values under PRBZT–PRBZT followed by RBCT–RBZT, FBZT–FBZT and FBCT–FBCT, respectively. PRBZT–PRBZT resulted in significantly higher grain (6.08; 6.19 t/ha) and stover yield (8.07; 8.22 t/ha) in maize during both years, however, it remained statistically at par with RBCT–RBZT and least under FBCT–FBCT. Harvest index was highest under PRBZT–PRBZT although non-significant among CETMs. P-fertilization significantly influenced the growth parameters, days taken to different phenological-stages and growth-indices (CGR, RGR, NAR). The P50+PSB+AMF+2FSP exhibited significantly higher grain (6.24; 6.37 t/ha) and stover yield (8.65; 8.98 t/ha) in maize over rest of the treatments during both years. Overall, PRBZT–PRBZT alongwith P50+PSB+AMF+2FSP proved vital for enhancing growth and yield of maize under MWCS in semi-arid Indo-Gangetic-plains.